Development of Educational Game-Based Learning Media in Natural Science Subjects at Madrasah Ibtidaiyah Jayapura - Fajar Dwi Mukti (Southeast Asian Journal of Islamic Education, 2022)
This research aimed to address the issue of educational technology in madrasah ibtidaiyah by producing an educational game-based learning media in the field of natural science in MI in Jayapura, Papua. The development method used in this research was the modified 4D Thiagarajan model. This research consisted of three stages: Define, Design, and Develop. The educational game-based learning media, named GALAKSI Application, was evaluated by validators to determine the feasibility of the learning media to be used in MI. The instrument used was a checklist questionnaire. The data obtained was qualitative data that was converted into quantitative data and then tabulated and analyzed descriptively to determine the quality of the developed product. The research results show that the educational game-based learning media GALAKSI for natural science subjects has been developed based on the assessment of validators. The assessment results show that the aspect of display quality obtained a percentage of 85%, the aspect of software engineering obtained a percentage of 81%, the aspect of curriculum obtained a percentage of 82%, the aspect of the material presentation obtained a percentage of 95%, the aspect of implementation obtained a percentage of 97%, the aspect of evaluation obtained a percentage of 93%, and the aspect of language obtained a percentage of 92%. Based on these data, it is classified as very good (SB). The results show that the GALAKSI Application educational game-based learning media can be used for self-learning by students.